Social network analysis in operations and supply chain management: a review and revised research agenda - Han, Y.; Caldwell, N. D. (Emerald, 2020)
Purpose Social network analysis (SNA) seeks to manage the connections between entities through investigating and understanding behaviours and relationships. This study demonstrates the increasing relevance of social network approaches to solving contemporary and looming operations management (OM) and supply chain management (SCM) problems; including the coordination operations challenges raised by increased connectivity. Design/methodology/approach The systematic literature review approach adopted here examines 63 papers in OM and SCM published between 2000 and 2019. To-date OM reviews on SNA have focussed on discussing archetypal supply chains, what differentiates this study is the focus on how value was created in other forms of chains and operations. Findings This study reveals that current SNA adoption in OM is dominated by a manufacturing style focus on linear, sequential value creation, with a resulting focus only on sequential interdependence. SNA studies on reciprocally co-ordinated value creation (e.g. many service and network operations) are shown to have been neglected and are linked to a new agenda on contemporary management issues. Research limitations/implications Beyond encouraging the use of SNA, this study seeks to re-orient SNA approaches towards how contemporary services and networks create value. Originality/value Through adopting a unique combination of approaches and frameworks, this study challenges extant work to offer a substantially revised agenda for SNA use in Operations and Supply Chain Management.
Keywords: Social Network Analysis; Social Network theory; Systematic Literature Review; Operations Management; Supply Chain Management